Controversial effects of tourism on economic growth: A spatial analysis on Italian provincial data. (June 2022) - De Siano, Rita; Canale, Rosaria Rita
Abstract: The aim of the paper is to estimate the contribution of tourism to per capita GDP growth taking into account the congestion that could arise from an excess of presences. The interaction of tourism with the territory is captured by a novel indicator of tourism pressure based on both the pre-existing congestion and the economic contribution the tourism sector provides to the resident population. Spatial analyses detecting interdependences across Italian data at NUTS3 level (2005–2018) reveal, as foreseeable, that tourism exerts beneficial effects on growth. However, the pressure indicator proves also the existence of nonlinear effects suggesting that an excess of tourism is detrimental for per capita income in the observed area and, due to the presence of spatial spillover, also in adjacent territories. Results provide the opportunity to reflect on the circumstance that tourism has an enormous potential in terms of growth effects, but it can be exploited until it comes into conflict with the needs of the resident population. Highlights: The paper evaluates to what extent tourism can be beneficial for economic growth. An indicator of social and physical interaction with the territory is presented. A standard and spatial analysis is applied to Italian provincial data. Results reveal that tourism has non-linear controversial effects on growth. Spatial spillovers on growth determined also by tourism congestion.